Cultivation techniques of yam influence the amount of primary and secondary metabolites - Krüger, David; Drell, Philip; Riekötter, Jenny; Altmannshofer, Johanna; Weber, Robert; Busl, Matthias; Epping, Janina; Weng, Alexander (Frontiers in Agronomy, 2026)
IntroductionAgriculture is an indispensable practice with a long history that dates back millennia. The cultivation of Chinese yam (Dioscorea polystachya Turczaninow) is of social importance but not yet optimized; the process is currently complex and labor-intensive. Notwithstanding, the plant is regarded as a promising supplementation for ensuring food security, even in the face of climate change. This is due to its nutritional value and its diverse contribution to the cultivation of food crops. MethodThe EKO-YAM project, presented in this work, is thus concerned with the implementation and evaluation of four different cultivation methods with regard to the content of primary and secondary compounds, as well as economic factors. ResultsThis study shows insights into the scientific monitoring of growing and the impact of different cultivation techniques on starch and secondary metabolites. DiscussionThe superordinate goal was the improvement of the growing of Dioscorea polystachya in terms of diet, metabolites, costs, and sustainability.